Indeks Reverse untuk Graf Koprima Prima - Abdurahim Abdurahim; Nuzla Af'idatur Robbaniyah; Andika Ellena Saufika Hakim Maharani (Mathematics Study Program, Faculty of Mathematics and Natural Science, Udayana University Gedung UKM, Ruang UKM 8 Lt 1, Kampus Bukit Jimbaran, Badung-Bali., 2026)
Let is a graph. The degree of a vertex in is the number of vertices adjacent to the vertex. While the reverse degree of a vertex in is the maximum degree of the vertex minus the degree of the vertex plus 1. In this paper, the reverse degree is given for the vertices of the coprime prime graph . Furthermore, several reverse indices of are given including First and Second Zagreb, Sum-Connectivity, Arithmetic-Geometric, Geometric-Arithmetic.